Meningkatkan Hasil Belajar Tari Melalui Metode Tutor Sebaya bagi Kelas VIII MTsN 11 Agam - Radhia Hanifa (SENDRATASIK UNP, 2023)
This study aims to explain and describe how to improve student dance learning outcomes using the peer tutor method in class VIII MTsN 11 Agam. This type of research carried out is class action research (PTK) which is carried out in 2 cycles. The subjects of the research were students of class VIIIF MTsN 11 Agam totaling 23 people. The data collection techniques used are observation and documentation. The results of this study show that dance learning using the peer tutor method is successful in improving the learning outcomes of class VIIIF MTsN 11 Agam students. It can be proven that before using the peer tutor method, the average score of students in the first cycle under KKM, which is 74.78 with KKM 78. Meanwhile, in cycle II, student learning outcomes with the peer tutor method increased by an average of 82.39.  So it can be concluded that the application of learning through this peer tutor method can improve the learning outcomes of MTsN 11 agam students.